Head-to-head comparison of Sonazoid and SonoVue in the diagnosis of hepatocellular carcinoma for patients at high risk - Huang, Jiayan; Gao, Ling; Li, Jiawu; Yang, Rui; Jiang, Zhenpeng; Liao, Min; Luo, Yan; Lu, Qiang (Frontiers in Oncology, 2023)
Objectives: To compare the diagnostic efficacy of SonoVue-enhanced and Sonazoid-enhanced ultrasound (US) for hepatocellular carcinoma (HCC) in patients at high risk. Methods: Between August 2021 and February 2022, participants at high risk for HCC with focal liver lesions were enrolled and underwent both SonoVue- and Sonazoid-enhanced US. Vascular-phase and Kupffer phase (KP) imaging features of contrast-enhanced US (CEUS) were analyzed. The diagnostic performance of both contrast agent-enhanced US according to the CEUS liver imaging reporting and data system (LI-RADS) and the modified criteria (using KP defect instead of late and mild washout) were compared. Histopathology and contrast-enhanced MRI/CT were used as reference standards. Results: In total, 62 nodules, namely, 55 HCCs, 3 non-HCC malignancies and 4 hemangiomas, from 59 participants were included. SonoVue-enhanced US had comparable sensitivity to Sonazoid-enhanced US for diagnosing HCC [80% (95% confidential interval (CI): 67%, 89.6%) versus 74.6% (95% CI: 61%, 85.3%), p = 0.25]. Both SonoVue and Sonazoid-enhanced US achieved a specificity of 100%. Compared with CEUS LI-RADS, the modified criteria with Sonazoid did not improve sensitivity for HCC diagnosis [74.6% (95% CI: 61%, 85.3%) versus 76.4% (95% CI: 63%, 86.8%), p = 0.99]. Conclusions: Sonazoid-enhanced US had comparable diagnostic performance to SonoVue-enhanced US for patients with HCC risk. KP did not considerably improve the diagnostic efficacy, whereas KP defects in atypical hemangioma may be pitfalls in diagnosing HCC. Further studies with larger sample sizes are needed to further validate the conclusions in the present study.